Development of automatic alkaloid removal system for dioscorea hispida - Hudzari, Razali; Asimi, Mohd Noor; Muhamad Fauzan, Anuar (2011)
Dioscorea hispida (D.hispida) is a poisonous plant which their tuber contains toxic poison and can be consumed after the poison or dioscorine is removed. The tubers were peeled, sliced and soaked in flowing water (river) up to 7 days during traditionally detoxified process. Due to the traditional processing methods for removal of dioscorine is difficult to practice, we develop two types of equipment (wavy and spin) based on their water circulation operations. This project consisted the stages of design, fabricate and testing for the development of stand alone dioscorine removal equipment. Survival of Cyprinus carpio fish in slicing tuber of D.hispida extraction was used as a tool for detection of dioscorine removal. Results indicate that water circulation of spin operation was more effective compared to wavy type based on their capability of increasing pH activity and survival of fish as in D.hispida tuber during 6 hours of detoxified process. Therefore, this unique equipment can reduce the preparation time and also handling process of detoxified D.hispida thus making it to be more hygienic as compared to the traditional method in which river is used as a medium for dioscorine removal. The manual operation for water inlet and outlet for dioscorine removal system will replace for automatic operation by using On / Off solenoid valve while the Peripheral Interface Controller (PIC) is use for controlling input and output signal from sensor, solenoid valve and motor pump. Conceptually, the system will enhance with automatic timer which will pour out the dirty water and refill new water from inlet automatically